A meta‐analysis of rate ratios for nocturnal confirmed hypoglycaemia with insulin degludec vs. insulin glargine using different definitions for hypoglycaemia. Issue 4 (13th December 2015) - Heller, S.; Mathieu, C.; Kapur, R.; Wolden, M. L.; Zinman, B.
Abstract: Aims: A prospective meta‐analysis of phase 3 trials showed lower rates of nocturnal hypoglycaemia with insulin degludec vs. insulin glargine. We investigated the consistency of the results across different definitions of hypoglycaemia. Methods: This post‐hoc, patient‐level meta‐analysis included six randomized, controlled, 26‐ or 52‐week phase 3a trials in insulin‐naïve participants with Type 2 diabetes mellitus (Type 2 diabetesinsulin naïve ), participants with Type 2 diabetes mellitus using basal−bolus therapy (Type 2 diabetesBB ) and those with Type 1 diabetes mellitus. We used three definitions of hypoglycaemia and different timescales for the nocturnal period. Rates were analysed for the entire core trial period, the 'maintenance period' only, and the extension trial set population. Analyses utilized a negative binomial regression model. Results: In Type 2 diabetesinsulin naïve participants, risk of nocturnal hypoglycaemia was significantly lower with insulin degludec vs. insulin glargine for all hypoglycaemia definitions and trial periods. Risk was also lower for the timescale 21.59–05.59, but not 00.01–07.59. For Type 2 diabetesBB, nocturnal hypoglycaemia rates were lower with insulin degludec vs. insulin glargine across all definitions, timescales and trial periods, with one exception. For individuals with Type 1 diabetes mellitus, nocturnal hypoglycaemia risk was significantly lower with insulin degludec during the maintenance period for the original definition (plasma glucose < 3.1 mmol/l, timescale 00.01–05.59) and in the extension trial set population for all hypoglycaemia definitions except for the nocturnal timescale 00.01–07.59. Conclusions: Compared with insulin glargine, insulin degludec is associated with lower rates of nocturnal hypoglycaemia in people with Type 2 diabetes mellitus, and similar or lower rates in Type 1 diabetes mellitus, across different definitions. What's new?: This meta‐analysis investigated the rate of nocturnal hypoglycaemia using different definitions of hypoglycaemia and of the nocturnal timescale in participants treated with insulin glargine or insulin degludec from phase 3a trials. Insulin degludec was associated with lower rates of nocturnal hypoglycaemia in participants with Type 2 diabetes mellitus, and lower or similar rates in participants with Type 1 diabetes mellitus across all definitions. Insulin degludec may help patients reach and maintain glucose targets, and reduce the frequency of nocturnal hypoglycaemia and its negative impact on patients' daily lives.